2015
DOI: 10.1037/xge0000055
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year follow-up of a study of memory for the attack of September 11, 2001: Flashbulb memories and memories for flashbulb events.

Abstract: Within a week of the attack of September 11, 2001, a consortium of researchers from across the United States distributed a survey asking about the circumstances in which respondents learned of the attack (their flashbulb memories) and the facts about the attack itself (their event memories). Follow-up surveys were distributed 11, 25, and 119 months after the attack. The study, therefore, examines retention of flashbulb memories and event memories at a substantially longer retention interval than any previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 101 publications
3
117
0
Order By: Relevance
“…For the features of age, gender, residence at the time of the attack, student membership at the time of the attack, political affiliation, race/ethnicity, and religion, there were no significant differences between those who completed all four surveys and (a) those who completed only the 2001 survey (see Hirst et al, 2015). Finally, although participants were recruited from across the United States, our sampling should not be viewed as representative of the American public.…”
Section: Methodsmentioning
confidence: 97%
“…For the features of age, gender, residence at the time of the attack, student membership at the time of the attack, political affiliation, race/ethnicity, and religion, there were no significant differences between those who completed all four surveys and (a) those who completed only the 2001 survey (see Hirst et al, 2015). Finally, although participants were recruited from across the United States, our sampling should not be viewed as representative of the American public.…”
Section: Methodsmentioning
confidence: 97%
“…As yet, such consistent findings have proven elusive. For instance, Talarico and Rubin (2003) and Hirst et al (2009, 2015) failed to find any correspondence between emotional state and consistency in their studies of FBMs of 9/11. Mahmood, Manier, and Hirst (2004) raised questions about distinctiveness by showing that the phenomenological quality of FBMs of the deaths of friends and lovers from AIDS remained the same whether one experienced multiple deaths or a single death.…”
Section: Factors Affecting Flashbulb Memoriesmentioning
confidence: 93%
“…Why is it that few Americans have trouble recollecting where they were when they learned about the attack of 9/11 (Hirst et al, 2015)? The specifics of the FBMs’ content may differ, but everyone has a memory.…”
Section: Factors Affecting Flashbulb Memoriesmentioning
confidence: 99%
“…Indeed, people will correct their memories to conform to acknowledged facts. For instance, Hirst et al (2015) found that the errors people made about the facts surrounding 9/11 tended to be corrected over time, in large part, because the media supplied the necessary corrective material. To be sure, errors can persist (Lewandowsky, Stritzke, Oberauer, & Morales, 2005), but Schwartz is right that people's recollections do not occur in a factual vacuum.…”
Section: Similarities and Differences Between Lived And Distant Semanmentioning
confidence: 97%